Fantasyland : how America went haywire : a 500-year history - Andersen, Kurt, 1954- (New York : Random House, 2017)
Now entering fantasyland -- Part I. The conjuring of America: 1517-1789 -- I believe, therefore I am right: the Protestants -- All that glitters: the gold-seekers -- Building our own private heaven on Earth: the puritans -- The God-given freedom to believe in God -- Imaginary friends and enemies: the early satanic panics -- The first me century: religion gets American -- Meanwhile, in the 18th century reality-based community -- Part II. United States of amazing: the 1800s -- The first great delirium -- The all-American fan fiction of Joseph Smith, prophet -- Quack nation: magical but modern? -- Fantastic business: the gold rush inflection point -- In search of monsters to destroy: the conspiracy-theory habit -- The war between states of mind -- Ten million little houses on the prairie -- Fantasy industrialized -- Part III. A long arc bending toward reason: 1900-1960 -- Progress and backlash -- The biggest backlash: brand new old-time religion -- The business of America is show business -- Big rock candy mountains: utopia in the suburbs and the sun -- The 1950s seemed so normal -- Part IV. Big bang: the 1960s and 70s -- Big bang: the hippies -- Big bang: the intellectuals -- Big bang: the Christians -- Big bang: politics and government and conspiracies -- Big bang: living in a land of entertainment -- Part V. Fantasyland scales: from the 1980s through the turn of the century -- Making make-believe more realistic and real life more make-believe -- Forever young: kids r us syndrome -- The Reagan era and the start of the digital age -- American religion from the turn of the millennium -- Our wilder christianities: belief and practice -- America versus the godless civilized world: why are we so exceptional? -- Magical but not necessarily christian, spiritual but not religious -- Blue-chip witch doctors: the re-enchantment of medicine -- How the mainstream enabled fantasyland: squishies, cynics and believers -- Anything goes -- unless it picks my pocket or break my leg -- Part VI. The problem with fantasyland: from the 1980s to the present and beyond -- The inmates running the asylum decide monsters are everywhere -- Reality is a conspiracy: the x-filing of America -- Mad as hell, the new voice of the people -- When the GOP went off the rails -- Liberals denying science -- Gun crazy -- Final fantasy-industrial complex -- Our inner children? They're going to Disney World! -- The economic dreamtime -- As fantasyland goes, so goes the nation
Now entering fantasyland -- Part I. The conjuring of America: 1517-1789 -- I believe, therefore I am right: the Protestants -- All that glitters: the gold-seekers -- Building our own private heaven on Earth: the puritans -- The God-given freedom to believe in God -- Imaginary friends and enemies: the early satanic panics -- The first me century: religion gets American -- Meanwhile, in the 18th century reality-based community -- Part II. United States of amazing: the 1800s -- The first great delirium -- The all-American fan fiction of Joseph Smith, prophet -- Quack nation: magical but modern ? -- Fantastic business: the gold rush inflection point -- In search of monsters to destroy: the conspiracy-theory habit -- The war between states of mind -- Ten million little houses on the prairie -- Fantasy industrialized -- Part III. A long arc bending toward reason: 1900-1960 -- Progress and backlash -- The biggest backlash: brand new old-time religion -- The business of America is show business -- Big rock candy mountains: utopia in the suburbs and the sun -- The 1950s seemed so normal -- Part IV. Big bang: the 1960s and 70s -- Big bang: the hippies -- Big bang: the intellectuals -- Big bang: the Christians -- Big bang: politics and government and conspiracies -- Big bang: living in a land of entertainment -- Part V. Fantasyland scales: from the 1980s through the turn of the century -- Making make-believe more realistic and real life more make-believe -- Forever young: kids r us syndrome -- The Reagan era and the start of the digital age -- American religion from the turn of the millennium -- Our wilder christianities: belief and practice -- America versus the godless civilized world: why are we so exceptional? -- Magical but not necessarily christian, spiritual but not religious -- Blue-chip witch doctors: the re-enchantment of medicine -- How the mainstream enabled fantasyland: squishies, cynics and believers -- Anything goes -- unless it picks my pocket or break my leg -- Part VI. The problem with fantasyland: from the 1980s to the present and beyond -- The inmates running the asylum decide monsters are everywhere -- Reality is a conspiracy: the x-filing of America -- Mad as hell, the new voice of the people -- When the GOP went off the rails -- Liberals denying science -- Gun crazy -- Final fantasy-industrial complex -- Our inner children? They're going to Disney World! -- The economic dreamtime -- As fantasyland goes, so goes the nation.
Includes index.
Keywords: National characteristics, American; Popular culture -- United States -- History; Cultura popular -- Estados Unidos -- Historia; United States -- Civilization; Estados Unidos -- Civilización